Penerapan Arsitektur Hijau dalam Desain Indoor Waterpark di Kota Makassar - Uleng, Ahmad; Nursyam, Nursyam; Bunawardi, Ratriana Said (TIMPALAJA : Architecture Student Journals, 2025)
Although many tourist attractions in Indonesia contribute to the country's foreign exchange, indoor theme parks, especially indoor water parks, have yet to open in Makassar and across Indonesia. This limits the variety of tourism options and opportunities to improve the local economy. The purpose of this study is to develop the concept of an "indoor water park" as a new destination in Makassar that offers diverse forms of entertainment and encourages the growth of the city's tourism. The methods used include literature research, site analysis, and the application of green architecture principles to reduce the use of new energy through a treatment system and the utilization of used water. The design results indicate that an indoor water park based on green architecture is feasible, as it can expand tourism options, make visitors more comfortable, and boost Makassar's economy.